Nursing Care for Mr. A and Mr. V With Diagnosis of Schizophrenia Risk Problems of Violent Behavior at Dr. Soeharto Heerdjan Mental Hospital Jakarta: Sidna Nurhalisza BSY, Fitria Prihatini, Elwindra - BSY, Sidna Nurhalisza; Prihatini, Fitria; Elwindra, Elwindra (Jurnal Persada Husada Indonesia, 2023)
The risk of violent behavior is a result or complication of hallucinations if left untreated. Violent behavior is one of the angry responses expressed by making threats, harming others, and/or damaging the environment. Based on data obtained by hallucinatory patients in the cassowary room as much as 99.7%, this data also includes data on the risk of violent behavior. This study used a type of descriptive qualitative research, namely by interview, observation and physical examination. General objectives in carrying out nursing care on clients at risk of violent behavior. From the results of the study, 5 diagnoses were found in Mr. A and 3 diagnoses in Mr. V. 3 of them were the same, namely the risk of violent behavior, sensory disorders, hallucinatory perception, and low self-esteem. In Mr. A, 2 different diagnoses were found, namely effective family coping and effective therapy regimen. In planning and implementation, strategies for implementing the risk of violent behavior are carried out, namely SP 1 controls PK by physical exercise to breathe deeply and hit pillows / mattresses, SP 2 controls PK by taking drugs, and SP 3 asks, refuses and expresses feelings in a good way. In Mr. V and Mr. A, the same intervention was carried out in diagnosing the risk of violent behavior, while in Mr. A also carried out hallucinatory SP, SP 1 controlled hallucinations by rebuking, SP 2 controlled hallucinations with drugs, and SP 3 controlled hallucinations by conversing. On Mr. V it was not done because the client felt that he did not experience hallucinations. Both clients can follow the author's direction. 2 Mr. A's diagnosis is not in theory, namely effective family coping and effective therapy regimen.